Should Psoriasis Patients be Screened for Heart Disease - De Deyn, Michelle; Guerin, Ciara; Moloney, Kevin; Roden, Yasmine; Nath, Neelam (Trinity Student Medical Journal, 2015)
Psoriasis is a systemic, immune-mediated disorder that manifests as chronic skin and joint inflammation. While the prevalence of psoriasis worldwide is 2%, its prevalence in developed countries is on average about 4.6%. Psoriasis is associated with cardiovascular disease (CVD). For this literature review, Pubmed and Medline were used to source articles using the keywords ‘psoriasis’ and ‘cardiovascular disease’. The inclusion criteria were studies with sample sizes of 100 or more published in English from 2000 onwards. Out of 1,657 papers retrieved, 37 were deemed relevant. Of these, 36 papers contained evidence in support of screening for CVD while one paper had evidence against screening for CVD. Substantial evidence suggested a higher CVD prevalence in psoriasis patients compared to populations without psoriasis. Furthermore, the risk of develop- ing CVD correlated highly with increased psoriasis severity and duration in addition to other CVD risk factors. The pathophysiological link between psoriasis and CVD is a common immunological pro-inflammatory state. In conclusion, psoriasis is an independent risk factor for CVD, particularly in younger patients with severe psoriasis, and is associated with increased mortality. Further research is required to better understand the relationship between psoriasis, traditional risk factors and development of CVD.